A panel analysis of FDI inflows and poverty reduction in ECOWAS sub region: Implication for the Sustainable Development Goal 1 - Aderemi, Timothy. A.; Sikwela, Misery M. (Asian Journal of Economic Modelling, 2025)
This study investigated the relationship between FDI and poverty reduction in the ECOWAS sub-region from 1990 to 2023. The study employed an ex-post-facto research design. Annual data were sourced from WDI and UNCTAD, respectively. Consequently, this study used the panel ARDL method to estimate the collected data. The findings revealed, among other things, that a long-run convergence existed between FDI and poverty reduction. FDI and poverty reduction had a negative relationship in the long run (β1 = -0.0040, t = 1.2393), but it was not significant. Trade openness and poverty reduction had a significant negative relationship (α2 = -0.0007, t = 2.5194). Policymakers of the ECOWAS sub-region should adopt stable economic policies to avoid FDI inflow-driven setbacks in poverty reduction in this area. Policymakers in the ECOWAS sub-region must develop trade policies to create active trade pathways with the global economy because trade openness negatively affects poverty reduction. Achieving SDG 1 (zero poverty) will be challenging for ECOWAS member states to accomplish before 2030 if FDI inflow-driven setbacks in poverty reduction are not addressed.